Карл Маркс та суспільне питання - Ерліх, Є. (Інститут держави і права ім. В.М. Корецького НАН України, 2005)
В статье раскрываются основные противоречия экономической теории Маркса, который использовал английскую классическую политэкономию без ее переосмысления вместе с ее односторонностью будучи великим ученым и пламенным политико-револлюционером у Маркса в соотношении с научным мышлением не всегда проигрывала политика. The article reveals the basic contradictictions of economy theory of Marx who used the English political economy without its reconsideration altogether with its unilaterality. Being a great scientist and ardent political revolutionary, in Marx’s theory politics always took the upper hand over his scientific thinking.